BIBLIOGRAPHIC REVIEW: ANOSMIA IN COVID-19 - Morgado Pereira, Anna Carolina Canellas (2020)
Abstract Brazil had the first recorded case of Coronavirus Disease 2019 (COVID-19) on February 26, 2020. Since the beginning of the pandemic, there was a lot of unknowledge about the disease and its consequences. Currently, it is known that the coronavirus can cause the symptoms of a common cold including fever, cough, sore throat, nasal congestion, malaise, fatigue, headache, myalgia and anosmia. This study aims to highlight the increased concern among physicians, due to the increasing number of reported cases of anosmia in patients with COVID-19, as it suggests direct viral damage to olfactory receptors and retrograde neuronal degeneration of the central conduction pathways. In this context, for the evaluation of a patient with olfactory loss, it is necessary to have an anamnesis that contains the time of loss, concomitant factors such as “severe acute respiratory syndrome coronavirus 2” infection (SARS-CoV-2), whether there is complete or partial absence (which characterizes hyposmia) and other associated nasal symptoms. In addition, as a diagnostic method, it is essential to evaluate the smell from the presentation of odorous substances to the patient and ask to name them. The complaint of decreased or total loss of smell during the current pandemic scenario shows an alert symptom that needs medical investigation to confirm the suspicion of SARS-CoV-2 infection with early diagnosis and control of the spread of the disease.